Suppression of Parathyroid Hormone in a Patient with Severe Magnesium Depletion - Sangeeta Mutnuri; Isaac Fernandez; Tina Kochar (Case Reports in Nephrology)
Hypomagnesemia is often associated with coexisting electrolyte abnormalities like hypokalemia and hypocalcemia. Hypocalcemia has been shown to be secondary to hypoparathyroidism induced by hypomagnesemia. Here, we discuss a case of a patient with severe hypomagnesemia and associated hypocalcemia. A 38-year-old lady was admitted to the hospital for weakness of lower extremities and an eventual fall. The exam was significant for decreased motor strength and some paresthesias. The laboratory data was significant for hypomagnesemia, hypokalemia, and low parathyroid level in the face of hypocalcemia. After replacing magnesium, the parathyroid hormone levels normalized and led to eventual correction of calcium levels without any additional calcium replacement therapy. There was complete symptom resolution with correction of electrolyte abnormalities. This case highlights the importance of looking for all associated abnormalities in a patient with hypomagnesemia and starting the replacement therapy by first replacing the magnesium and then the others as needed. Replacing the magnesium alone may correct the hypoparathyroidism and eliminate the need for calcium replacement.